2011
DOI: 10.1007/s00125-011-2341-z
|View full text |Cite
|
Sign up to set email alerts
|

Coupling factor 6-induced activation of ecto-F1Fo complex induces insulin resistance, mild glucose intolerance and elevated blood pressure in mice

Abstract: Aims/hypothesis Despite advances in pharmacological treatments, diabetes with hypertension continues to be a major public health problem with high morbidity and mortality rates. We recently identified a circulating peptide coupling factor 6 (CF6), which binds to the plasma membrane ATP synthase (ecto-F 1 F o complex), resulting in intracellular acidosis. We investigated whether overexpression of CF6 contributes to diabetes and hypertension by intracellular acidosis. Methods Transgenic mice overexpressing CF6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…However, CF6 attenuates prostacyclin generation via the inhibition of cytosolic phospholipase A 2 , 16 nitric oxide generation via the upregulation of asymmetric dimethylarginine or the inhibition of endothelial nitric oxide synthase phosphorylation 45,46 and the PI3K/Akt cascade. 24 Therefore, the rapid effects of estrogen, such as the increase in nitric oxide and the induction of the PI3K-Akt cascade, may antagonize the action of CF6. This issue remains to be clarified in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CF6 attenuates prostacyclin generation via the inhibition of cytosolic phospholipase A 2 , 16 nitric oxide generation via the upregulation of asymmetric dimethylarginine or the inhibition of endothelial nitric oxide synthase phosphorylation 45,46 and the PI3K/Akt cascade. 24 Therefore, the rapid effects of estrogen, such as the increase in nitric oxide and the induction of the PI3K-Akt cascade, may antagonize the action of CF6. This issue remains to be clarified in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the TG mice is described elsewhere. 24 Briefly, the gene expression of CF6 mRNA was upregulated by 1.94 ± 0.27 times in body tissues, such as the heart, pancreas, spleen, kidneys and stomach, in TG mice compared with WT mice. The plasma level of total (human plus mouse) CF6 was twice as high in TG mice as in WT mice.…”
Section: Methods Animalsmentioning
confidence: 99%
“…Briefly, the introduced gene product was released outside of the cells by a secretion signal upstream from the mature human CF6 (Asn33-Ala108) and was expressed in overall tissues by the human elongation factor 1 promoter. CF6 mRNA expression was 7 upregulated by 1.94±0.27 times in overall tissues, including the heart and kidney, in the TG compared with wild-type mice (WT), and the plasma level of total CF6 was twice as high in the TG as in the WT (11). The intracellular pH value, as measured by 31 P-magnetic resonance spectroscopy, was decreased by 0.1 unit in skeletal muscle and liver of the TG (11).…”
Section: Cell Culturementioning
confidence: 96%
“…CF6 mRNA expression was 7 upregulated by 1.94±0.27 times in overall tissues, including the heart and kidney, in the TG compared with wild-type mice (WT), and the plasma level of total CF6 was twice as high in the TG as in the WT (11). The intracellular pH value, as measured by 31 P-magnetic resonance spectroscopy, was decreased by 0.1 unit in skeletal muscle and liver of the TG (11). For histological analysis, mice were sacrificed killed by cervical dislocation under anesthesia with intraperitoneal administration of 0.3 mg/kg medetomidine, 4 mg/kg midazolam, and 5 mg/kg butorphanol.…”
Section: Cell Culturementioning
confidence: 99%
“…CF6 functions are believed to be mediated by CF6 binding to the plasma membrane-bound ATP synthase, ecto-F1F0 complex, resulting in proton import and acidosis, whichin turn increases activated Rac1, a member of the Rho family of GTPases [3]. CF6 has several functions: it acts as a pro-atherogenic molecule in the cardiovascular system [4], regulated by estrogen in saltsensitive hypertension and cardiac systolic dysfunction in mice [3]; it attenuates exercise-induced physiological cardiac hypertrophy by inhibiting PI3K/Akt signaling in mice [5]; it plays a crucial role in the development of insulin resistance and hypertension [6]; and it appears to be a novel molecule for the pathogenesis and treatment of stroke [7]. Studies have shown an elevated plasma level of CF6 in patients with essential hypertension, diabetes mellitus, end-stage renal disease, acute myocardial infarction, and coronary heart disease [8]; however, research on CF6 in spontaneously hypertensive rats (SHRs) is mainly in vascular smooth muscle cells (VSMCs) and vascular endothelial cells [9,10].…”
mentioning
confidence: 99%